2023
DOI: 10.1136/bmjopen-2022-069500
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in children with neurodevelopmental conditions attending a publicly funded developmental assessment service: findings from the Sydney Child Neurodevelopment Research Registry

Abstract: ObjectivesEarly developmental assessment is crucial for effective support and intervention. This study examined factors that contribute to (a) older child age when caregivers first became concerned about their child’s development and (b) older child age at the point of entry into developmental and diagnostic assessment. We also quantified how factors contributed to risk of children not receiving an assessment by 5 years and considered the acceptability of electronic data capture for families.DesignThis cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…There is a delicate balance between timeliness and accuracy when providing diagnosis and intervention. Although no current guideline exists for how long ADHD or autism diagnosis should take, these findings and previous work (Boulton et al, 2023) emphasise the need for improved education and training on the diverse spectrum of ADHD and autism symptoms. Caregivers require education as they may be the first to identify developmental concerns, and specialist training for GP's, psychologists, and paediatricians has the potential to reduce diagnostic delays.…”
Section: Diagnostic Delaymentioning
confidence: 91%
“…There is a delicate balance between timeliness and accuracy when providing diagnosis and intervention. Although no current guideline exists for how long ADHD or autism diagnosis should take, these findings and previous work (Boulton et al, 2023) emphasise the need for improved education and training on the diverse spectrum of ADHD and autism symptoms. Caregivers require education as they may be the first to identify developmental concerns, and specialist training for GP's, psychologists, and paediatricians has the potential to reduce diagnostic delays.…”
Section: Diagnostic Delaymentioning
confidence: 91%
“…Any child who lives in the defined geographical regions and/or who is an existing hospital patient, regardless of family income, is eligible to be assessed (Hodge et al, 2021; Patel et al, 2021). A broader description of the clinic cohort is available elsewhere (Boulton et al, under review). The lead clinician in the service (N.S.)…”
Section: Methodsmentioning
confidence: 99%
“…Information on reason for referral was obtained from the clinical reports, as identified by the referring external healthcare professional. Caregiver reason(s) for concern were obtained from the intake questionnaire (for details, see Boulton et al, under review) or reported during clinical interviews with clinicians. Both information sources were included in the evaluation of caregiver perceived assessment needs and were coded into the referral variables shown in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing prevalence rates associated with neurodevelopmental conditions, such as autism (Maenner et al, 2023), and growing awareness of needs, have contributed to numerous studies highlighting the significant demand and subsequent wait time for clinical services (Boulton et al, 2023). Families can spend years waiting to receive their first multi‐disciplinary developmental assessment (Boulton et al, 2023). There is a growing need to understand how these assessments can then lead to relevant support pathways for families (Munro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Anonymous surveys of caregivers of children with suspected or diagnosed neurodevelopmental conditions have found that children can have relatively high levels of access to pediatricians, general medical practitioners and speech pathologists, but may have considerably less access to behavioral interventions and mental health supports (Sapiets et al, 2022). This is despite children with neurodevelopmental conditions commonly showing significant co‐occurring mental health symptoms (Boulton et al, 2023). Given existing guidelines and recommendations for early intervention (Association, 2022; Trembath et al, 2022), it is crucial to understand what supports caregivers can access while they wait for their developmental assessment.…”
Section: Introductionmentioning
confidence: 99%